2019
DOI: 10.1108/ijdrbe-06-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Flood resilience in Malaysian cities: a case study of two towns in Johor state

Abstract: Purpose This paper has carried out a case study of two flood-prone towns in Johor state, Malaysia, to understand how resilient the residents and local authorities were in dealing with the flood disasters in terms of their ability to anticipate, mobilize institutional resources, adapt and respond. Design/methodology/approach This research conducted semi-structured interviews with flood-affected residents, flood disaster managers and planners, and assessed land use regulations and institutional strengths to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…The estimated total loss due to these disasters was RM 1.5 billion of which, RM 237.1 million was for damaged infrastructure alone (Hamzah et al 2012;Tam et al 2014). A total of 11,724 victims in the Dec 2006 ood event and 7,915 victims in Jan 2007 were evacuated (Hamzah et al 2012;Tam et al 2014;Karki 2019). In some cases, ood victims had to move to another relief center as the evacuation centers were also ooded.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated total loss due to these disasters was RM 1.5 billion of which, RM 237.1 million was for damaged infrastructure alone (Hamzah et al 2012;Tam et al 2014). A total of 11,724 victims in the Dec 2006 ood event and 7,915 victims in Jan 2007 were evacuated (Hamzah et al 2012;Tam et al 2014;Karki 2019). In some cases, ood victims had to move to another relief center as the evacuation centers were also ooded.…”
Section: )mentioning
confidence: 99%
“…It was found that the main cause of the ood was due to a large amount of rainfall, geographically low laying area, rapid land-use changes, and tidal effect (Tam et al 2014;Karki 2019). The ood started on Dec 19, 2006, until Jan 16, 2007, where the rst wave had inundated most of the Kota Tinggi town.…”
Section: )mentioning
confidence: 99%
“…Being one of the wettest places on Earth, the Maritime Continent (MC) separates the Indian Ocean from the Pacific and encompasses the countries of Indonesia, Malaysia and the Philippines, among others. This region experiences significant extreme precipitation (Hai et al., 2017; Warlina & Guinensa, 2019), which, combined with the high vulnerability of the local population (Abd Majid et al., 2019; Cabrera & Lee, 2020; Karki, 2019; Takama et al., 2017), can lead to severe consequences. An accurate prediction of extreme precipitation in the MC is therefore of crucial importance for society.…”
Section: Introductionmentioning
confidence: 99%
“…the local population (Abd Majid et al, 2019;Cabrera & Lee, 2020;Karki, 2019;Takama et al, 2017), can lead to severe consequences. An accurate prediction of extreme precipitation in the MC is therefore of crucial importance for society.…”
mentioning
confidence: 99%
“…In Malaysia, there is inequality in the level of advancement and development for assessing the different components of flood risk: flood hazard and exposure assessment studies are more advanced and developed. In contrast, flood vulnerability modeling and assessments are underdeveloped (Karki, 2019; Zakaria et al , 2017).…”
Section: Introductionmentioning
confidence: 99%